2001
DOI: 10.22358/jafs/70115/2001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of feeding raw vs extruded soyabean supplemented or unsupplemented with sulphur amino acids on performance, pancreatic trypsin activity and morphological parameters of the jejunum in rats

Abstract: The effect of extrusion of soyabean seeds and sulphur amino acid (AA) supplementation on trypsin inhibitor (TI) and lectin activity, and on the histology and microbiology of the jejunum were studied. Wistar rats were fed semi-purified diets containing 10% of soyabean seeds: raw (R) or extruded at 160°C (E) and unsupplemented or supplemented with 0.3% (AA) (met+cys, 1:1). Extrusion reduced TI activity in seeds from 25.0 to 11.8 TUI/mg. Extrusion of soyabean seeds also reduced agglutination activity against huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Similar effects of extrusion or boiling (Leontowicz et al, 1998) of faba bean and pea seeds have been observed. Soyabean seeds are less sensitive to extrusion at the same temperature than faba bean (Leontowicz et al, 2001a). Sulphur AA (0.3%o) significantly improved performance of rats fed both raw or extruded faba bean seeds, which is in agreement with other studies.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar effects of extrusion or boiling (Leontowicz et al, 1998) of faba bean and pea seeds have been observed. Soyabean seeds are less sensitive to extrusion at the same temperature than faba bean (Leontowicz et al, 2001a). Sulphur AA (0.3%o) significantly improved performance of rats fed both raw or extruded faba bean seeds, which is in agreement with other studies.…”
Section: Resultssupporting
confidence: 91%
“…Lower lectin activity in raw faba bean and lower E. coli number in the rat jejunum caused less significant morphological changes in the small intestine than in rats fed on raw soyabean (Leontowicz et al, 2001a) or pea (Leontowicz et al, 2000). Elimination of lectin activity during extrusion of faba bean seeds and AA supplementation significantly improved intestinal crypt depth, villi length and width.…”
Section: Resultsmentioning
confidence: 99%
“…This was seen as reduction of intestinal villi and hyperplasia within crypts, leading to impaired absorption in the intestine. Previous studies have shown that administration of lectins to animals per os leads to pancreatic hypertrophy and degenerative changes in organs such as kidney and liver [35, 36, 37]. The negative impact was not seen in the presence of raw soy phytates, which reduce the absorption of phosphorus by forming complexes with it.…”
Section: Resultsmentioning
confidence: 95%